COGNITIVE REHABILITATION IN MULTIPLE SCLEROSIS. Issue 11 (14th October 2015) - Campbell, Jamie; Cercignani, Mara; Langdon, Dawn; Rashid, Waqar
Abstract : Background/aims: To explore the feasibility and efficacy of computerised, home-based cognitive rehabilitation in patients with multiple sclerosis using neuropsychological assessment and structural and functional MRI techniques. Materials, methods or case report: 38 patients with MS and evidence of cognitive impairment on the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) test battery were enrolled and randomly assigned to undergo computerised cognitive rehabilitation (n=19) for six weeks or to a control condition (n=19). All patients underwent MRI at baseline (T1) and post-intervention (T2). Changes in cortical activations were explored using an n-back fMRI paradigm. Results: Compared to baseline, patients in the treatment group showed significant improvement in the Brief Visuospatial Memory Test at T2 (p=0.035) and exhibited altered cortical fMRI activations compared to controls. Conclusion: Our preliminary data support the hypothesis that home-based, computerised cognitive rehabilitation is a feasible and effective approach to improving cognitive performance in patients with MS and may reflect underlying changes in brain activations. BICAMS is a sensitive and easy to administer tool for identifying cognitive impairment in MS in the outpatient setting. Identification of cognitive impairment may have important treatment implications in the future.